Implementation of Line Balancing to Increase the Productivity of the Box Aspect Production Process - Arifin, Defitria Sabrina Firdaus; Saifuddin, Joumil Aidil (Journal La Multiapp, 2025)
In the manufacturing industry, the balance of the production trajectory is an important factor in increasing productivity and efficiency. In the production process at PT XYZ, there are problems with the balance of the production trajectory at the workstation, so it is necessary to determine the optimal production trajectory so that the load on the workstation can be evenly distributed and able to reduce idle time. The Ranked Positional Weight (RPW) and Region Approach (RA) methods were chosen in this study. The main bottleneck was found at the hole cutting stage, where tool limitations caused output differences between manual and machine processes. This imbalance resulted in idle time which affected the overall production efficiency. The analysis results show that the application of RPW and RA methods is able to improve trajectory efficiency by optimizing the number of work stations and reducing idle time. The analysis results state that the company can achieve a trajectory efficiency of 88.48% and reduce the balance delay from -16.67% to 15,73% and a smoothness index of 611,25%.